(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
In this Study of domestic and foreign mineral oils used after adding a mixture of solutions (HCl + Methanol + Butanol) in limited proportions in the treatment process for oils such as Thuraya oil, Zawia F Gasoline oil, Goldex Super Plus oil, LUKOIL oil for recycling, and these chemical solutions were used to remove contaminants and impurities from oils; As the process of reacting solutions with oils can be used to convert used (burned) oils into reuse by reacting oils with acid to form different compounds. Methanol could be also being used to convert burnt oils into more effective oils, and butane was used in the oil distillation process to remove heavy compounds and impurities from the oil and improve its quality according to the results obtained, by using Flash point. Several physiochemical techniques such as kinematic viscosity, specific gravity, flash point and using FT-IR spectroscopy to track changes after treatment; And the degree of flash to study the specifications of the types of manufactured oils (domestic and foreign) that are recycled in each case and to know the extent of their suitability for new use. The viscosity of the unused oil was at a low temperature of 40 and 100 for the 2 types of Zawia F Gasoline oil and Goldex Super Plus oil. This decrease is explained by the addition of these chemical solutions to remove contaminants and impurities from the oils in limited proportions, the results show the action of hydrochloric acid to interact with the oil and break it down into glycerides and free fatty acids. Methanol acts as an antifreeze and helps in improving the quality of the oils. Pollutants and impurities from oils in small proportions and re-use as essential oil. Note that HCl makes the oil lose 22.25% of its viscosity value, and this is a negative result for using hydrochloric acid. However, in general, the properties of the recycled oil in both cases is considered good and are still at the required level suitable for use as a base oil according to local and international specifications.